Susceptibility of Olea europaea L. varieties to Xylella fastidiosa subsp. pauca ST53: systematic literature search up to 24 March 2017. (19th April 2017) - ,; Baù, Andrea; Delbianco, Alice; Stancanelli, Giuseppe; Tramontini, Sara
Abstract: EFSA was requested by the European Commission to produce a report on the susceptibility of olive varieties to the Apulian strain of Xylella fastidiosa (subsp. pauca strain CoDiRO, ST53). A systematic literature search identified 21 references providing results of primary research studies on olive plants infected (naturally or artificially) by ST53. From experimental infectivity studies and from surveys in olive orchards, converging lines of evidence indicate tolerance of the Leccino variety to ST53 infections, although no long‐term observations on yield are available yet. While the variety Leccino can become infected with the pathogen, it develops milder symptoms compared to those observed on susceptible varieties (e.g. Cellina di Nardò, Ogliarola salentina). Also, the size of the X. fastidiosa bacterial populations measured in Leccino‐infected plants is lower compared to susceptible olive varieties. Preliminary results show that tolerance or resistance traits can also be found in other olive varieties. New research is now in place in the EU to study the level of susceptibility of many olive varieties to ST53 infections, therefore more relevant results will become available in the coming years.